2009
DOI: 10.1203/pdr.0b013e3181a283a0
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Changes of the Heart After Neonatal Dexamethasone Treatment: Studies in 4-, 8-, and 50-Week-Old Rats

Abstract: Dexamethasone (Dex), for prevention of chronic lung disease in preterm infants, showed potential negative long-term effects. Studies regarding long-term cardiovascular effects are lacking. We investigated possible histopathological myocardial changes after neonatal Dex in the young and adult rat heart. Rats were treated with Dex on d 1, 2, and 3 (0.5, 0.3, and 0.1 mg/kg) of life. Control-pups received saline. At 4, 8, and 50 wk after birth rats were killed and anatomic data collected. Heart tissue was stained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
2
28
1
Order By: Relevance
“…In addition, total body weight was lower in Dex-treated rats, which suggests that neonatal Dex treatment had a negative effect on organ growth and development. This was similar to findings in earlier studies (13)(14)(15). The differences in weight may be partially due to nutritional problems in the days after the neonatal treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, total body weight was lower in Dex-treated rats, which suggests that neonatal Dex treatment had a negative effect on organ growth and development. This was similar to findings in earlier studies (13)(14)(15). The differences in weight may be partially due to nutritional problems in the days after the neonatal treatment.…”
Section: Discussionsupporting
confidence: 91%
“…It was shown that in rats a 3-d course of Dex significantly suppressed proliferative activity of cardiomyocytes in the first week of life. At 50 wk of age this resulted in a lower number of cardiomyocytes in the heart, cardiomyocyte hypertrophy and increased interstitial fibrosis (13)(14)(15).…”
mentioning
confidence: 99%
“…Our results indicated that DEX-treated rats had significantly lower body weights than SAL-treated rats up to 14 wk of age, and no reduced body weight mentioned afterwards, indicating neonatal DEX administration may cause transient growth retardation, and there might exit a catch-up body weight gain in adult life. Previous studies described lower heart weights in rats aged 50 wk following neonatal DEX administration (12). However, in the present experiment, no alterations in relative Figure 6.…”
Section: Discussioncontrasting
confidence: 56%
“…Increase in heart size during the fetal and early postnatal period occurs mainly by hyperplasia of cardiomyocytes [17] while later it is mainly due to cell hypertrophy [18]. Cardiomyocyte hyperplasia during the perinatal period may be impaired by various nutritional, hemodynamic and humoral factors [19], which are more common in ELBW children. A recent study showed that resuscitation with 100% oxygen compared to room air led to the increase of myocardial damage in an animal model [20].…”
Section: Discussionmentioning
confidence: 99%